Geographical Analysis of Agricultural and Livestock Production in Wadi Al-Shati Municipality within the Framework of the General Average for Libya during the Period 2001–2007 (Al-Farooq Journal of Sciences, 2026)
The research aimed to analyze agricultural and livestock production in Wadi Al-Shati Municipality within the context of Libya’s overall average during the period 2001–2007. It also aimed to identify the spatial and temporal variations in production levels, examine changes in the numbers of sheep, goats, and camels, and compare the municipality’s production level with the national level in Libya. The research employed the descriptive, analytical, and comparative approaches, relying on statistical data related to agricultural and livestock production during the research period. Quantitative and statistical methods were also used to process and analyze the data, utilizing tables, percentages, averages, and rates of change to interpret the results and highlight spatial and temporal variations.The research concluded that there was a clear spatial variation in agricultural and livestock production levels among the different areas of Wadi Al-Shati Municipality. It also revealed temporal changes in production levels during the study period, ranging between increases, decreases, and fluctuations depending on the type of product. The comparison with Libya’s overall average showed variations in the municipality’s relative position according to the type of crop or livestock product. The research also found spatial variations in the distribution of sheep, goats, and camels among the municipality’s areas and between the 2001 and 2007 censuses.The research recommended improving the utilization of agricultural and livestock resources, rationalizing irrigation water use, supporting livestock activities and veterinary services, and providing updated and regular statistical data. It proposed establishing a geographic database for agricultural and livestock production, conducting future research on the factors influencing spatial and temporal variations in production, and employing Geographic Information Systems (GIS) and remote sensing in future studies.